Semantik Dan Kearifan Lokal: Analisis Permainan Tradisional Kota Tasikmalaya Sebagai Warisan Budaya - Aas Salamah; Dwi Sartika; Ghina Ayu Salsabila; Salsabila Putri Rahmawati; Aveny Septi Astriani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This study aims to describe the lexical meaning contained in the names of traditional games. Traditional games analyzed by lexical semantic studies have six traditional game names, namely gobak sodor, egrang, ucing sumput, péclé, dam-daman, sapintrong, ucing baledog, and sorodot gaplok. This study used qualitative descriptive method. Qualitative research is research that produces descriptive data in the form of written or spoken words and observable behavior. This research data is the name of the traditional game. Data collection techniques in the form of literature research. While the research technique uses a reading and record technique. The results of this study contained several terms from six game names analyzed using lexical semantic studies, namely "gobak", "sodor", "egrang", "ucing", "sumput", "péclé", "méclé", "dam", "sakti", "lasut", "baledog", "hompimpah", "suten", "sorodot", and "gaplok".